Safety‐related outcomes of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery board certification system for expert surgeons. (26th April 2017) - Otsubo, Takehito; Kobayashi, Shinjiro; Sano, Keiji; Misawa, Takeyuki; Ota, Takehiro; Katagiri, Satoshi; Yanaga, Katsuhiko; Yamaue, Hiroki; Kokudo, Norihiro; Unno, Michiaki; Fujimoto, Jiro; Miura, Fumihiko; et al.
Abstract: Background: We investigated safety‐related outcomes of hepatobiliary pancreatic (HBP) surgeries performed after establishment of the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery (JSHBPS) board certification system for expert surgeons. Methods: We analyzed post‐HBP surgery mortality data obtained from annual safety reports provided by board‐certified training institutions between 2012 and 2015. Results: The 90‐day mortality rate for the 53, 929 high‐level HBP surgeries performed at board‐certified training institutions was 1.7%. The 30‐day mortality rates for 2012, 2013, 2014, and 2015 were 0.9%, 0.7%, 0.6%, and 0.6%, respectively, and the 90‐day mortality rates were 2.1%, 1.8%, 1.6%, and 1.3%, respectively, with significant decreases in both. The surgeries with high 4‐year cumulative mortality rates were left hepatic trisectionectomy (10.3%), hepatopancreatectomy (7.6%), liver transplant recipient surgery (6.7%), hepatectomy with extrahepatic bile duct resection (4.6%), and right hepatic trisectionectomy (4.5%). Over the 4‐year period, the number of operations increased, but the 90‐day mortality rates for these surgeries, with the exception of right trisectionectomy, decreased. Conclusions: The JSHBPS board certification system for expert surgeons has significantly decreased mortality subsequent to high‐level HBP surgeries. Reducing mortality associated with high‐risk HBP surgeries will be our next challenge. Abstract : Highlight On behalf of the JSHBPS Safety Management Committee, Otsubo and colleagues report the results of their first analysis of safety‐related outcomes of the recently established JSHBPS board certification system for expert surgeons. Data spanning 2012–2015 indicate that the board certification system has significantly decreased mortality subsequent to high‐level hepato‐biliary‐pancreatic surgery.